Crosstalk between neuroinflammation and ferroptosis: Implications for Parkinson’s disease progression - Guo, Xiangyu; Wei, Ran; Yin, Xunzhe; Yang, Ge (Frontiers in Pharmacology, 2025)
Parkinson’s disease (PD) is a common neurodegenerative disorder characterized by the degeneration of dopaminergic neurons and the aggregation of α-synuclein. Neuroinflammation is triggered by the activation of microglia and astrocytes, which release pro-inflammatory factors that exacerbate neuronal damage. This inflammatory state also disrupts iron homeostasis, leading to the occurrence of ferroptosis. Ferroptosis is characterized by lipid peroxidation of cell membranes and iron overload. Abnormal accumulation of iron in the brain increases oxidative stress and lipid peroxidation, further aggravating neuroinflammation and damage to dopaminergic neurons. Natural products have garnered attention for their antioxidant, anti-inflammatory, and neuroprotective properties, with many plant extracts showing promising therapeutic potential in PD research. This study further investigates the potential therapeutic roles of various natural products in regulating neuroinflammation and ferroptosis. The results suggest that natural products have significant therapeutic potential in modulating the interaction between neuroinflammation and ferroptosis, making them potential treatments for PD. Future research should further validate the safety and efficacy of these natural compounds in clinical applications to develop novel therapeutic strategies for PD.